(untitled) (Journal of Asian Development Studies, 2025)
Advancement in human evolution appears to be in the hands of growth in education. Different disciplinary procedures and learning philosophies build the instructional approach towards inclusive classroom teaching. In the wake of a comprehensive study being completed in a classroom setting, dialogue and discussions are arranged. Over the last 20 years, different adjustments to teaching and learning practices in inclusive learning environments have revealed that educational quality and learning outcomes have improved much for students in developing nations worldwide. The research objectives were to identify different teaching adaptations teachers use for students with impairments regarding reading, writing, speaking, hearing and listening in creating inclusive classrooms in primary level schools. According to School Information System (www.sis.punjab.gov.pk), Tehsil Gojra had total 113 male primary schools where 206 teachers were teaching. By maintaining a 95% confidence level and confidence interval 5, and using www.surveysystem.com, sample size of 134 was determined. Convenient method of sampling was used to select the respondents. A structured questionnaire was used to collect essential information from respondents. Statistical Package for the Social Sciences (SPSS) processed the collected information. ’Use computer games’ with mean score of 2.22, ’shorten writing assignments’ with mean score of 2.16, ’allow extra response time for processing’ with mean score of 2.18, ’emphasizing key points’ with mean score of 2.17 and ’provide material in large or braille print’ with mean score of 2.18 were widely used adaptations by the teachers in inclusive learning regarding reading, writing, speaking, hearing and listening needs respectively. The data demonstrated how important teachers were in fostering an inclusive learning environment and how crucial it was to use various tactics and adaptations to help struggling students.